2016
DOI: 10.1002/ajpa.23105
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the jacchus group of Callithrix marmosets based on complete mitochondrial genomes

Abstract: Callithrix nuclear and mtDNA phylogenies frequently result in polytomies and paraphyly. Here, we present a well-supported phylogenetic tree based on mitochondrial genome sequences, which facilitates the understanding of the divergence of the jacchus marmosets. Our results demonstrate how mitochondrial genomes can enrich Callithrix phylogenetic studies by alleviating some of the difficulties faced by previous mtDNA studies and allow formulation of hypotheses to test further under larger genomic-scale analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 67 publications
7
42
0
Order By: Relevance
“…Because most of Callithrix species do not have equivalent or more similar than expected climatic niches, we can assume that they have a certain degree of niche differentiation, leading to partially or nonoverlapping climatic requirements. Given the recent diversification of this taxa (Malukiewicz et al, ; Perelman et al, ; Schneider et al, ) and the current hypothesis that Callithrix diversification arose predominantly from the isolation of ancestral forms (Kinzey, ; Marroig, Cropp, & Cheverud, ), our results suggest a rapid climatic niche differentiation after species’ isolation. Niche similarities tests, however, can underestimate climatic niches (and consequently the overlap between them) because they are based on the current occupied distribution of organisms, which is potentially reduced by biotic factors and dispersal limitations.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Because most of Callithrix species do not have equivalent or more similar than expected climatic niches, we can assume that they have a certain degree of niche differentiation, leading to partially or nonoverlapping climatic requirements. Given the recent diversification of this taxa (Malukiewicz et al, ; Perelman et al, ; Schneider et al, ) and the current hypothesis that Callithrix diversification arose predominantly from the isolation of ancestral forms (Kinzey, ; Marroig, Cropp, & Cheverud, ), our results suggest a rapid climatic niche differentiation after species’ isolation. Niche similarities tests, however, can underestimate climatic niches (and consequently the overlap between them) because they are based on the current occupied distribution of organisms, which is potentially reduced by biotic factors and dispersal limitations.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, Because most of Callithrix species do not have equivalent or more similar than expected climatic niches, we can assume that they have a certain degree of niche differentiation, leading to partially or nonoverlapping climatic requirements. Given the recent diversification of this taxa (Malukiewicz et al, 2017;Perelman et al, 2011;Schneider et al, 2012) and the current hypothesis that Callithrix diversification arose predominantly from the isolation of ancestral forms (Kinzey, 1982;Marroig, Cropp, & Cheverud, 2004), our results suggest a rapid climatic niche differentiation after species' isolation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our results revealed that in marmosets as other animals, both host environment and taxonomy shape the gut microbiome [60][61][62][63]. However, host environment in this study showed stronger influence on marmoset GMC than host taxonomy, perhaps due to how closely related Callithrix species are as a recent primate radiation [64,65]. As host environment had the strongest effect on marmoset GMC within our study, the below discussion focuses largely on this factor.…”
Section: Discussionmentioning
confidence: 63%
“…South American Callithrix marmosets (Figure ) also demonstrate extensive hybridization between subspecies and species, in variable environments and with different levels of reproductive isolation, therefore making them an additional comparative primate model for considering hominin hybridization. Speciation of current Callithrix marmosets began approximately 3.7 Ma, with the most recent divergence event taking place less than 1 Ma between C. jacchus and C. penicillata . Experimental interspecific crosses revealed different levels of reproductive isolation between different species pairs, as captive C. jacchus × C. penicillata hybridized with relative ease, but physical anomalies such as blindness were common when other species pairs were crossed .…”
Section: The Human Genome Shows Extensive Evidence Of Introgression Tmentioning
confidence: 99%